Analysis of Variables that Affect the Initial Return of IPO Stocks on the Indonesian Stock Exchange in 2023 and 2024 - Zulhelfi, Zulhelfi (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
In the process of listing shares for the first time, there is often an extraordinary increase in share prices. This extraordinary price increase certainly also provides benefits for investors. Given the phenomenon of high stock price increases, many studies have been conducted to determine the variables that are very instrumental in causing the increase in stock prices. Many studies have been conducted to determine the causes of high initial return, but the findings are different and inconsistent so the most dominant factor in determining the initial return cannot be determined. In this study, we will analyze the influence of variables of stock index changes, stock issuance value, oversubscription, PBV, PER, stock trading frequency, market capitalization, and stock trading volume, and whether they affect the initial return of IPO shares. Of the 8 variables observed, two variables have a positive and significant effect, namely stock issuance value and oversubscription, one variable has a negative and significant effect, namely stock trading frequency, four variables have a negative but insignificant effect, namely JCI, PBV, PER and market capitalization, and one variable has a positive but insignificant effect, trading volume.